2011
DOI: 10.1002/cbf.1786
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia‐modified albumin levels in newborn jaundice before and after phototherapy

Abstract: The aim of our study was to assess the effect of phototherapy (PT) on ischaemia-modified albumin (IMA) and malondialdehyde (MDA) levels in hyperbilirubinemic full-term newborns. The study was performed on 36 full-term infants exposed to PT. The babies were aged 3 to 13 days. IMA and MDA levels of the babies were determined before and after PT, by a colorimetric assay. IMA levels before and after PT were found as 0.424 ± 0.290 and 0.531 ± 0.262 absorbance units, respectively. Although IMA levels after PT were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Bilirubin is a well known antioxidant and when bound to human albumin scavenges free radical thereby protecting albumin bound fatty acids and most likely the protein itself from oxidation. 20 We however found no significant difference in bilirubin and albumin levels between the HD groups, which may partially explain the similar results of IMA in both groups. An invitro study of Erdern et al reported an increase of IMA and MDA levels with phototherapy, suggesing that this may be due to high levels of bilirubin which acts as an antioxidant.…”
Section: Discussionmentioning
confidence: 41%
“…Bilirubin is a well known antioxidant and when bound to human albumin scavenges free radical thereby protecting albumin bound fatty acids and most likely the protein itself from oxidation. 20 We however found no significant difference in bilirubin and albumin levels between the HD groups, which may partially explain the similar results of IMA in both groups. An invitro study of Erdern et al reported an increase of IMA and MDA levels with phototherapy, suggesing that this may be due to high levels of bilirubin which acts as an antioxidant.…”
Section: Discussionmentioning
confidence: 41%